Hybrid stator flux locus strategy for enhancing torque control in high-speed induction motors - Syed Ahmad Zawawi, Syed Abrar (2025)
This thesis presents an enhanced Direct Torque Control (DTC) strategy for three-phase induction motors aimed at improving dynamic torque control performance in high-speed operations by modifying the stator flux locus. DTC is widely adopted in industrial applications due to its simple structure and fast torque response. However, it suffers from notable limitations such as high torque ripple and inadequate torque control under high speed conditions. These drawbacks are primarily due to the use of hysteresis controllers and the limitation imposed by a circular stator flux locus, which restricts the angular frequency of the stator flux vector and degrades the ability to maintain the load angle, thus reducing torque control effectiveness at high speeds. To overcome the poor torque dynamic control performance at high speeds, this research proposes a simple modification of the stator flux locus from a circular into a hexagonal by adjusting the flux hysteresis bandwidth with an appropriate bandwidth. A hybrid control of flux locus is proposed where the hexagonal flux locus is controlled during the dynamic conditions (acceleration and a sudden large torque demands), while the circular flux locus is controlled during steady-state conditions (constant speed and torque demands). By modifying the flux locus into a hexagonal shape, the angular velocity of the stator flux vector can be increased beyond its conventional limit, thereby maintaining the load angle and hence the motor torque at high speeds. This approach also promotes the application of the most optimal voltage vectors (the voltage vectors that have the largest tangential component) to the stator flux vector are frequently applied and this enables the transition of phase voltages from a PWM to almost a six-step voltage in satisfying the torque demand, during acceleration mode. On the other hand, the flux locus transforms back to a circular locus which retains lower current harmonic distortions when the speed reaches to its demand (steady-state condition). The hybrid flux locus control strategy is adopted in the simple DTC structure where the mechanism to modify the flux locus is enabled when the DTC applied the hexagonal` bandwidth and detects a dynamic condition when a large speed error is detected. Simulation and experimental results confirm performance gains, including a 31.25% faster dynamic response, elimination of steady-state speed error by 3.57%, and a 16.7% reduction in steady-state operating current. The benefit of this research is the improvements can be achieved without the use of complex flux weakening and space vector modulation (SVM) strategy, making the approach a practical and scalable solution for high-performance industrial drives and electric vehicle applications.